RESPON MAHASISWA TERHADAP PENUGASAN MUSIKALISASI PUISI MELALUI MEDIA SOSIAL - Ely Nurmaily (Fakultas Sastra Universitas Negeri Malang, 2018)
Abstract: This study aims to find a new method in learning and teaching literature to the students in practical terms and to perceive the students’ response toward the assignment of musical poetry project through social media. Studying literature in the writer's environment (Lampung) is a monotonous activity for students. By having a musical poetry project, students have some creativities in creating, composing, showing and recording and then uploading the result through social media. In the end, the hidden talents of the students can be seen and they are expected to become musicians, writers, event organizers, and others. In addition, the students also give positive response to this method. Assignment of musical poetry project through social media can improve students’ creativity. permalink/DOI: dx.doi.org/10.17977/um015v46i12018p029